Medicinal herbs and multiple sclerosis: Overview on the hard balance between new therapeutic strategy and occupational health risk - Costantini, Erica; Masciarelli, Eva; Casorri, Laura; Di Luigi, Marco; Reale, Marcella (Frontiers in Cellular Neuroscience, 2022)
Multiple sclerosis (MS) is an autoimmune disease characterized by demyelination and axonal loss of the central nervous system (CNS). Despite its spread throughout the world, the mechanisms that determine its onset are still to be defined. MS is triggered by a combination of factors such as immunological, genetical, viral, environmental and not at least the exposure to chemicals. Studies providing indication about relationship between environmental exposure to pesticides and incidence of MS disease are few, fragmentary, and discordant. The demand for medicinal plants, with potential beneficial effects for MS patients, is constantly increasing as the consequent need for their greater productivity. Keeping in mind the pathological mechanisms of MS and the oxidative damages and mitochondrial dis-functions induced by pesticides raised the question if pesticides, used to increase agricultural productivity, and their residues, present in medicinal plants, may increase the risk of developing MS in both workers and consumers. The aim of this article is to provide an overview on therapeutic potential of medical plants and on pesticide exposure as possible risk factor for the development of MS disease, for former workers and consumers of medicinal plants.